Entrepreneurship in prison: hope for the women imprisoned of the Female Recovery Center of Ananindeua-Pará, Brazil (Research, Society and Development, 2020)
This study sought to verify the perception of the inmates who work at the Social Cooperative Work of Feminine Art Entrepreneurship, located in the Female Reeducation Center in the municipality of Ananindeua - Pará, regarding the type of work developed, as a form of social reintegration. Qualitative research of an exploratory nature was used, with the use of data collection techniques by interviews, followed by an analysis of the content of the statements. As a result, it was identified that the motivation of prisoners to work in the Cooperative is to obtain income for their own support and that of their families, the occupation of time and the remission of the sentence. In addition, aspects such as improved self-esteem, the refuge of the cell environment and the importance of handicrafts for the mental health of these women were found. And it was concluded that despite the difficulties faced, cooperative women see in this type of business a possibility for the future, after serving their sentence, as well as favoring social reintegration.